write V as a function of h. Simplify the function so that you can express it as a polynomial in h.

V = ( 2-r^2 / 3 ) h and h / (2-r) = 5/2

I got h = (10-5r)/2

and then V = (5*r^3)-(10*r^2)-(10*r)+20

somehow it's not correct?

Printable View

- February 8th 2010, 06:46 PMyoumugglesrearranging equations
write V as a function of h. Simplify the function so that you can express it as a polynomial in h.

V = ( 2-r^2 / 3 ) h and h / (2-r) = 5/2

I got h = (10-5r)/2

and then V = (5*r^3)-(10*r^2)-(10*r)+20

somehow it's not correct? - February 8th 2010, 07:19 PMapple123
Looks like you've made a small multiplication error somewhere.

You are right that h / (2 - r) = 5/2 is the same as (10 - 5r)/2. But you can make things easier for yourself if you simplify that further. Why not just write (5/2)(2-r) = h?

Now, take V, and replace h with what you found.

(( 2 - r^2)/3)(5/2)(2-r).

Now, to make things look simpler, let's pull out that 1/3 and the 5/2 and simplify them.

(1/3)*(5/2) = 5/6

So now we have (5/6)(2-r^2)(2-r)

You can multiply out (2 - r^2) and (2 - r), right? Then either multiply each term of your answer by 5/6 or leave the 5/6 factored out in front. - February 8th 2010, 08:31 PMearboth